Association between iron deficiency anemia and risk of hearing loss among female patients: a multi-institutional cohort study - Chen, I-Wen; Yu, Ting-Sian; Lai, Yi-Chen; Chang, Ying-Jen; Hung, Kuo-Chuan (Frontiers in Nutrition, 2025)
BackgroundIron deficiency anemia (IDA) represents the most prevalent nutritional deficiency worldwide, disproportionately affecting women of reproductive age. Emerging evidence suggests IDA may have underappreciated consequences for sensory organ function, particularly hearing. The inner ear’s high metabolic demands and intricate vascular supply may render it vulnerable to chronic IDA and resulting tissue hypoxia. This study examined the association between IDA and hearing loss risk in female patients.MethodsThis retrospective cohort study used the TriNetX Analytics Network Platform database (2010–2022) with five-year follow-up. Female patients with IDA were identified by hemoglobin below 12 g/dL, serum ferritin below 30 ng/mL within 3 months, and ICD-10-CM diagnosis codes. Controls had hemoglobin above 12 g/dL, ferritin above 30 ng/mL, and no IDA codes. Propensity score matching created 71,003 matched pairs balanced for demographics, comorbidities, and laboratory parameters. The primary outcome was hearing loss development within 5 years. Time-to-event analyses used Kaplan–Meier methods and Cox proportional hazards regression.ResultsPatients with IDA demonstrated significantly higher hearing loss incidence compared to matched controls (0.98% versus 0.81%, hazard ratio [HR]: 1.50, 95% CI 1.34–1.67, p < 0.001). Risk was highest within the first year (HR 2.79, 95% CI 2.00–3.88) and remained significant at 5 years. Dose–response analysis revealed greater risk with severe anemia (hemoglobin below 10 g/dL). Age-stratified analysis showed consistent associations across age groups, and findings were replicated in male patients.ConclusionIDA is independently associated with increased hearing loss risk in women, with a temporal gradient suggesting acute effects during active deficiency. These findings suggest routine audiological assessment should be considered for patients with IDA, particularly during the first year following diagnosis.